Levantamiento del velo corporativo una revisión histórica de las sentencias de la superintenencia de sociedades (2018)
The application criteria in which the Colombian legal system bases the application of the dismissal of the legal personality of the mercantile companies will be examined, also known as the disregard of the legal entity, due to its origin in the United States. To determine these criteria, we will conduct a historical analysis of the emergence and development of this figure, both internationally, where we will emphasize the main countries that contributed and enriched its structure, as in Colombian, analyzing its arrival, development and current application. Finally, we will carry out an examination of a sample of judgments of the Superintendency of Companies, in which the criteria that are taken into account by this administrative entity that has jurisdictional functions are considered in a timely manner, when deciding on processes where requests the removal of the corporate veil when the partners have committed unlawful acts, using the constitutional benefits generated by the Colombian legal system for commercial companies.